جريمة الامتناع عن تحرير عقد الإيجار – دراسة مقارنة - عجمي, ليالي راهي (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
The lease contract is classified among the nominate contracts that enjoy widespread application within legal practice. It is characterized by a notable flexibility in form, as the Iraqi legislator does not prescribe a specific modality for its conclusion. The contract is deemed valid upon mutual consent of the parties, regardless of whether such agreement is expressed in writing, orally, through intelligible gestures, or by any other means that clearly convey intent. Even in instances where the legislator mandates written documentation—as stipulated in the Real Estate Lease Law—this requirement does not render the contract formalistic in nature. Rather, it serves a regulatory function, enabling competent authorities to exercise oversight over such agreements. Nonetheless, the Iraqi legislator has treated the failure to document a lease contract as a punishable infraction. Legal sanctions are imposed on individuals who neglect to deposit a copy of the contract with designated official entities. This violation is addressed in Paragraph Two of Article 23 of the amended Real Estate Lease Law No. 87 of 1979, which stipulates that the non-complying party may be subject to imprisonment or a monetary fine if the contract is neither documented nor submitted to the Real Estate Tax Department, the Information Office, or the local police station within thirty days from the date of its execution. A comparative legislative analysis reveals that most legal systems do not criminalize such omissions, with the notable exception of Egyptian legislation. The latter obligates the lessor to draft a lease contract containing mandatory particulars and imposes penalties on those who fail to comply with this obligation. The research problem lies in the specific scope of criminalization in the crime of refusing to draw up a lease agreement. This crime – according to the Iraqi Rent Law – includes specific areas stipulated by the law and does not include the entire territorial scope of the state. Also, to determine whether the real estate tax departments are fulfilling their role in monitoring the implementation of the provisions of this law or not? And to determine the extent of proportionality between the penalty prescribed by the Iraqi legislator for the perpetrator of this crime and the seriousness of the act committed by the offender? The selection of this offense as the subject of inquiry stems from its legal and practical significance, particularly due to its direct bearing on safeguarding the rights of contracting parties. Moreover, the specific criminal conduct it entails distinguishes it from other offenses related to lease agreements. The scarcity of specialized studies addressing this issue further underscores the necessity of a comprehensive investigation that fills this gap in legal literature and contributes meaningfully to academic discourse.